Great grand mothers: the female portrait sculpture of Aphrodisias: origins and meaning - Long, Tracey Elizabeth (2014)
This thesis sets out to explore the influences on and meaning of early imperial female portrait sculpture and statues of Aphrodisias in Asia Minor. This group is unlike any other. There survives a rich amount of contextual evidence as well as some unique portraits with unusual features. They appeared at a time of social change for women and as the first images of imperial wives and mothers emerged from Rome. Local artists exploited this imagery in the city of Aphrodite, the ultimate mother of the Julio-Claudian dynasty. These portraits have only ever been studied as part of the corpus of statues that includes those of males; as a homogenous group with little new to say. In the home of the most significant mother of the time, I propose that the portraits disproportionately emphasise motherhood and reflect the new-found power enjoyed by some of the earliest empresses.